2011
DOI: 10.1139/h11-012
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Sedentary Behaviour Guidelines for Children and Youth

Abstract: The Canadian Society for Exercise Physiology (CSEP), in partnership with the Healthy Active Living and Obesity Research Group (HALO) at the Children's Hospital of Eastern Ontario Research Institute, and in collaboration with ParticipACTION, and others, has developed the Canadian Sedentary Behaviour Guidelines for Children (aged 5-11 years) and Youth (aged 12-17 years). The guidelines include a preamble to provide context, followed by the specific recommendations for sedentary behaviour. The entire development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
408
2
17

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 458 publications
(440 citation statements)
references
References 19 publications
13
408
2
17
Order By: Relevance
“…27 Individual-level estimates were determined by looking at the differences in caloric expenditure of screen time (1.25 METS 28 ) and active play. This was done for a 60 minutes/day period as well as a period of time that corresponded to the difference between the benchmark for screen time (2 hours/day) 29 and the average daily screen time of 11-year-old Canadians (5.8 hours/day). 5,19,30 The 3.8-hour difference between the screen time benchmark and the average screen time of 11 year olds is consistent with the benchmark for active play, which is that children engage in active play for several hours daily.…”
Section: Active Play and Screen Timementioning
confidence: 99%
“…27 Individual-level estimates were determined by looking at the differences in caloric expenditure of screen time (1.25 METS 28 ) and active play. This was done for a 60 minutes/day period as well as a period of time that corresponded to the difference between the benchmark for screen time (2 hours/day) 29 and the average daily screen time of 11-year-old Canadians (5.8 hours/day). 5,19,30 The 3.8-hour difference between the screen time benchmark and the average screen time of 11 year olds is consistent with the benchmark for active play, which is that children engage in active play for several hours daily.…”
Section: Active Play and Screen Timementioning
confidence: 99%
“…4,5 Corresponding guidelines for children 5-17 years of age recommend at least 60 minutes of daily moderate-to-vigorous physical activity (MVPA) and no more than 2 hours of daily recreational screen time. 6,7 Nationally-representative data from the 2009-2013 Canadian Health Measures Surveys (CHMS) indicated that 73% of 3-4 year olds met the PA guidelines, but only 22% met the screen time recommendation. 8 Compliance with the PA guidelines was much lower in 5 year olds (30%), although 76% met the screen time guideline.…”
mentioning
confidence: 99%
“…For the physical activity guidelines, it is recommended that children aged <1 year are physically active several times a day (5), children aged 2-4 years are physically active at any intensity for at least 180 minutes a day (5), and children and youth aged 5-17 years are physically active at moderate-to vigorous-intensity for at least 60 minutes a day (8). For the sedentary behaviour guidelines, it is recommended children aged <2 years engage in no screen time (6), children 2-4 years engage in under 1 hour a day of screen time (6), and children 5-17 years engage in 2 hours a day or less of recreational screen time (7).…”
mentioning
confidence: 99%